2018
DOI: 10.7554/elife.32785
|View full text |Cite
|
Sign up to set email alerts
|

A transcription factor collective defines the HSN serotonergic neuron regulatory landscape

Abstract: Cell differentiation is controlled by individual transcription factors (TFs) that together activate a selection of enhancers in specific cell types. How these combinations of TFs identify and activate their target sequences remains poorly understood. Here, we identify the cis-regulatory transcriptional code that controls the differentiation of serotonergic HSN neurons in Caenorhabditis elegans. Activation of the HSN transcriptome is directly orchestrated by a collective of six TFs. Binding site clusters for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 110 publications
9
65
0
1
Order By: Relevance
“…Two orthologous POU homeobox genes, C. elegans unc-86 and mouse Brn3a, both act as terminal selectors of neuronal identity. Previous work has shown that unc-86 and Brn3a are required during development to initiate the terminal differentiation program of a number of different neuronal classes [7][8][9][10][11][12][13][15][16][17][18]. In both worms and mice, the terminal gene batteries controlled by these POU homeobox genes are similar and include Figure S3.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Two orthologous POU homeobox genes, C. elegans unc-86 and mouse Brn3a, both act as terminal selectors of neuronal identity. Previous work has shown that unc-86 and Brn3a are required during development to initiate the terminal differentiation program of a number of different neuronal classes [7][8][9][10][11][12][13][15][16][17][18]. In both worms and mice, the terminal gene batteries controlled by these POU homeobox genes are similar and include Figure S3.…”
Section: Discussionmentioning
confidence: 98%
“…The activity of subtype-specific cofactors could also explain the incomplete penetrance of the Brn3a mutant phenotype that we described here. Subtypespecific partnering of mouse Brn3a with other transcription factors is also very reminiscent of C. elegans unc-86, which specifies the identity of related neurons through the interaction with neuron-class-specific cofactors [8,[10][11][12][13]40]. In some of these cases, removal of unc-86 alone shows partially penetrant phenotype, and it is only the joint removal of unc-86 and its cofactor that results in fully penetrant loss-of-identity phenotypes [8,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MGE, POa and septum). The role of Er81 in the dopaminergic Hobert, 2009) (Cave et al, 2010) and serotoninergic cell fates (Lloret-Fernandez et al, 2018) and here, in cholinergic cell identity, suggest a general regulatory mechanism of Er81 on the emergence of functional neuromodulatory systems in the developing brain.…”
Section: Control Of the Cholinergic Cell Identitymentioning
confidence: 66%